Breast milk, weight loss and hyperbilirubinemia in fitllterm newborn infants in the first week of life - Achmad Surjono, Achmad Surjono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
The objectives were to find out the proportion of hiperhilinthinemia in term of breast-fed newborn infants, the figure of their weight loss and any significant difference in weight loss between hyperbilirubinemic group as compared with control.The subjects consist of a total of 210 singleton full-term newborn babies delivered in Dr. Sardjito Hospital from January 1 to June 30, 1992, with 5 minute Apgar score more than six and on permission of the mothers.The serum total bilirubin (TB) and unbound bilirubin (UB) were measured on day 3 and 5. TB concentration was measured spectrophotometrically and UB level was determined by peroxidase oxidation method using UB-analyzer, an automated micromethod. Body weight and first week conditions of the infants were recorded daily. Mean (ÃÂ± SD) TB and UB values in the third day were 10.30 ÃÂ± 3.42 mg% and 0.24 ÃÂ± 0.16 p.g%, respectively. The proportion of hyperbilirubinemia was 11.9%, in whom 44% received phototherapy (UB level 0.5 pg%). The mean weight loss (%) was 3.95 ÃÂ± 1.84: No statistically significant difference on weight loss was found between hyperbilinthinemic and control group (p > 0.05).Hyperbilirubinemia in breast-fed term newborn infants can be considered a minor problem. Considering the benefit of mother milk, in particular for exclusive breast feeding, temporary cessation of breast feeding is not needed. On the contrary, more frequent suckling is advised with a close observation of UB levels.Key Words : breast feeding fulltenn infants hyperbilirubinemia unbound bilirubin weight loss